2010
DOI: 10.1007/s00226-010-0337-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extractives on vibrational properties of African Padauk (Pterocarpus soyauxii Taub.)

Abstract: Extractives can affect vibrational properties tan1 (damping coefficient) and E'/2 (specific Young's modulus) but this is highly dependent on species, compounds, and cellular locations. This paper investigates such effects for African Padauk (Pterocarpus soyauxii Taub.), a tropical hardwood with high extractives content and a preferred material for xylophones. 5 groups of 26 heartwood specimens with large, yet comparable, ranges in vibrational properties were extracted in different solvents. Changes in vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 21 publications
1
39
0
4
Order By: Relevance
“…Therefore, we assume that extractives are responsible for the variations of viscoelastic properties between our specimens. The influence of extractives on damping coefficient was also revealed by other researchers Obataya et al, 2000;Brémaud et al, 2010a;Minato et al, 2010), by changing the extractive content either through extraction or impregnation.…”
Section: Relation Between Vibrational Properties Mfa and Heartwood Fsupporting
confidence: 55%
See 4 more Smart Citations
“…Therefore, we assume that extractives are responsible for the variations of viscoelastic properties between our specimens. The influence of extractives on damping coefficient was also revealed by other researchers Obataya et al, 2000;Brémaud et al, 2010a;Minato et al, 2010), by changing the extractive content either through extraction or impregnation.…”
Section: Relation Between Vibrational Properties Mfa and Heartwood Fsupporting
confidence: 55%
“…A "standard relation" was established to describe the statistical relation between these properties (Ono and Norimoto, 1983), based on more than 1000 specimens taken from 20 softwood species. The validity of this relation has also been shown on hardwood species (Brémaud et al, 2010a). Recently, using selective extractions, Brémaud et al (Brémaud et al, 2010a;Brémaud et al, 2010b) showed that wood extractives modified this "standard relation" by changing the intercept of the line, not its slope.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations